面向知识经济大潮的领导者素质问题 = A study on the leaders' qualities in a knowledge economy environment - 张增良 Zhang, Zengliang (2011)
Being a completely new economic form, knowledge economy is exerting more and more strikingly affects on all aspects of the society. What qualities leaders should possess to meet the challenge of knowledge economy becomes an important research topic. This thesis thoroughly discussed the essential qualities leaders (mainly the leaders of counties, cities and enterprises) should own in a knowledge economy environment. The methodologies and methods for a comprehensive improvement in the leaders' qualities have been systematically studied. Based on a thorough study of knowledge economy and the newest research results, this thesis systematically discussed the origins, concepts and characteristics of knowledge economy and their influences on various aspects of the society. Based on abundant information analysis and typical case studies, this thesis has initially revealed the five basic qualities (global brain, foresight, creativeness, alllife- study and moral quality) that leaders at every level must own to suit the corresponding characteristics of knowledge economy, i.e., network, globalization and creative ability, etc. The author objectively analyzed the current situations of the leaders at various positions from different aspects, such as moral characteristics, educational background, management ability, creative ability and global viewpoint, etc. New concepts and standards for the choice and use of leaders have been put forward. The ways and methods for the selection, examination, and training of leaders have also been presented in details.